A haplotype block downstream of plasminogen is associated with chronic and aggressive periodontitis. (11th September 2017) - Munz, Matthias; Chen, Hong; Jockel‐Schneider, Yvonne; Adam, Knut; Hoffman, Per; Berger, Klaus; Kocher, Thomas; Meyle, Jörg; Eickholz, Peter; Doerfer, Christof; Laudes, Matthias; Uitterlinden, André; et al.
Abstract: Aim: The intronic variant rs4252120 in the plasminogen gene ( PLG ) is known to be associated with aggressive periodontitis (AgP) and atherosclerosis. Here, we examined the chromosomal region spanning PLG for associations with both chronic periodontitis (CP) and AgP. Materials and Methods: The association of PLG candidate rs4252120 was tested in a German case–control sample of 1, 419 CP cases using the genotyping assay hCV11225947 and 4, 562 controls, genotyped with HumanOmni BeadChips. The German and Dutch sample of AgP cases ( N = 851) and controls ( N = 6, 836) were genotyped with HumanOmni BeadChips. The North American CP sample ( N = 2, 681 cases, 1, 823 controls) was previously genotyped on the Genome‐Wide Human SNP Array 6.0. Genotypes were imputed (software Impute v2), and association tests were performed using an additive genetic model adjusting for sex and smoking. Results: Rs4252120 was not associated with CP. However, a haplotype block downstream of PLG and not in linkage disequilibrium with rs4252120 ( r 2 = .08) was associated with both AgP (rs1247559; p = .002, odds ratio [OR] = 1.33) and CP ( p = .02, OR = 1.15). That locus was also significantly associated with PLG expression in osteoblasts ( p = 6.9 × 10 −5 ). Conclusions: Our findings support a role of genetic variants in PLG in the aetiology of periodontitis.